Teaching Practicum Experiences: Pre-service English Teachers’ Self-Reflections of Their Professional Growth - Yuliani Dwi Astuti; Nur Arifah Drajati (Journal of Innovation in Educational and Cultural Research, 2022)
Reflection is one of essential components which could develop prospective teachers’ professional practice. By capturing participants’ self-reflections in their teaching practicum experiences, this study aims to explore the nature of student-teacher individual reflection throughout their teaching experience in the teaching practicum. Narrative data garnered through multiple semi-structured interviews had been scheduled for 30-60 minutes per interview session. The interview-derived narrative data analysed by using IPA (interpretative phenomenological analysis) and CDA (critical discourse analysis). These analytical frameworks were to explore the longitudinal nature dimensions of three pre-service English teachers during their teaching practicum experiences. The finding of this study indicated that most of the reflections created the participants awareness that learning environments, teacher ability and creativity, managing the time and classroom have pivotal role in teaching process. Drawing on this, the practical implication of the study is that teachers not only develop their professionalism, but they must also develop skills, creativity, and understand what students need during a teaching practicum.